Legal Protection for Concurrent Creditors Reviewed from the Principle of Business Continuity and the Principle of Justice - Hambali Hambali; Supot Rattanapun (PT. Multidisciplinary Press Indonesia, 2025)
This article discusses legal protection for concurrent creditors in bankruptcy proceedings by reviewing the application of the going concern principle and the principle of fairness. Bankruptcy is a condition that requires the management of debtor assets to ensure payment of debts to creditors. However, concurrent creditors are often in a disadvantageous position in terms of payment priority, thus requiring special legal protection. The going concern principle provides an opportunity for companies to continue operating and increase the value of assets in order to optimize payments to concurrent creditors. Meanwhile, the principle of fairness ensures a fair and proportional distribution among all creditors without any arbitrary actions. Through this analysis, the article concludes that the application of both principles can improve protection for concurrent creditors and create a fairer bankruptcy process. Recommendations include improving regulations to clarify creditor protection mechanisms, stricter supervision of the implementation of the principle of fairness, and optimizing the application of the going concern principle to increase the value of assets for concurrent creditors.